OP0275 Fibromyalgia prevalence and impact on disease activity scores in rheumatoid arthritis patients who are unresponsive to biological treatment. (15th June 2017) - Ghib, LJ; Tamas, MM; Felea, I; Damian, L; Filipescu, I; Mociran, A; Simon, S-P; Muntean, L; Rednic, S
Abstract : Background: Rheumatoid arthritis (RA) treatment uses a treat-to-target strategy and disease assessment is based on disease activity scores (DAS) such as the DAS28 1 . Biological drugs have proven highly effective for RA treatment in clinical studies 2, however, in real life settings, comorbidities such as fibromyalgia (FM) might influence treatment response assessed by DAS28. Objectives: In this study we determined FM prevalence and the impact on disease activity scores in patients with RA undergoing biological treatment and if higher tender joint (TJC) correlates with lower pain threshold in patients with active RA who did not satisfy FM criteria. Methods: We performed a cross sectional study on RA patients undergoing biological treatment who presented in our department for a 6 month period. DAS28 was calculated for all patients. FM diagnosis was considered positive if patients satisfied both the ACR 1990 and ACR 2010 FM Criteria. Pain pressure thresholds (PPT) were measured at the level of the medial knee joint line, mid sternum and middle of the tibia with a manual dolorimeter. Depression, Anxiety, Stress 21 scale (DASS21) and Health Assessment Questionnaire (HAQ) were applied to all patients. Results: 112 patients were included, 84.8% women, mean age 55.6 (SD 11.6) with a mean disease duration of 14.5 (SD 8.5) years. Acording to DAS28ESR scores 54 (48.2%) had moderate disease activity and 26 (23.2%) had high disease activity. 17 (21.5%) of patients with DAS28ESR scores over 3.2 satisfied FM criteria. FRA and RA groups did not differ significantly concerning age, disease and biological treatment duration, seropositivity, BMI or DASS21 scores. FRA patients had significantly higher values for DAS28 ESR, DAS28 CRP, PGH and HAQ, but similar values for SJC, ESR and CRP compared to RA patients (Table 1 ). In RA patients without FM, TJC correlated significantly with number of trigger points (r=-0.3), PPT at knee (r=-0.4), sternum (r=-0.3) and tibial level (r=-0.2). Conclusions: Fibromyalgia is present in a significant percent of patients who are unresponsive to biological treatment as assessed by DAS28 score. Subjective components of DAS28 are significantly higher in FRA compared to RA patients, suggesting that disease assessment should be performed using objective measures in these patients. In patients with active disease despite biological treatment whitout FM, lower pain thresholds are correlated with TJC, suggesting a possible involvement of central pain mechanisms. References: Smolen JS, et al. Treating rheumatoid arthritis to target: recommendations of an international task force. Ann Rheum Dis. 2010;69(4):631–637. Tvete IF, et al. Comparing Effects of Biologic Agents in Treating Patients with Rheumatoid Arthritis: A Multiple Treatment Comparison Regression Analysis. PLoS One. 2015;10(9):e0137258. Disclosure of Interest: None declared